Developing Immunoniosomes (INs): Antibody and Fab conjugations of niosomal nanoparticles via UV-NBS and EDC/NHS chemistry for treating glioblastoma cells - Nilufer Cakir; Hatice Oncel; Aylin Ozkan; Dilan Bicak; Sibel Akgun Bas; Nur Mustafaoglu (International Journal of Pharmaceutics: X)
Antibody-conjugated nanoparticles (ACNPs), particularly immunoliposomes (ILs), have gained significant attention in cancer treatment due to their enhanced efficacy and superior tissue penetration. However, their high production costs and technical challenges underscore the need for more cost-effective alternatives. Niosomes, with their lower production costs, improved stability, and biocompatibility, have emerged as promising alternatives to liposomes in drug delivery. This study introduces immunoniosomes (INs), a novel class of antibody-conjugated niosomes, through two conjugation strategies: (i) UV-NBS, a site-specific covalent conjugation method utilizing an indole ring structure for moderate binding to the variable regions of antibodies and Fab fragments, and (ii) EDC/NHS chemistry, which conjugates antibodies to carboxylated niosomes via primary amines on lysine sidechains. Bevacizumab, a monoclonal antibody targeting VEGF and approved for the treatment of various cancers including glioblastoma multiforme (GBM), was used as a model therapeutic. Both Bevacizumab and its Fab fragment were conjugated to niosomes and evaluated in U87 glioma cells (overexpressing VEGF) and human umbilical vein endothelial cells (HUVECs) (representing normal VEGF expression). Physicochemical characterization of the conjugated niosomes confirmed hydrodynamic sizes ranging from 100 to 200 nm, neutral surface charge, and dispersity indices below 0.5—properties critical for effective cellular penetration and drug delivery. Cellular toxicity assays, conducted at a 10× dilution from commonly reported concentrations, highlighted the role of the autocrine loop in U87 glioblastoma cells. Importantly, specific Nio-Fab conjugate formulations, created through both site-specific and randomized conjugation strategies, exhibited enhanced cytotoxicity toward U87 cells while sparing healthy endothelial HUVEC cells. In summary, this research establishes novel conjugation strategies to produce stable, site-specific, and randomized antibody-niosomal conjugates with enhanced half-life and selective toxicity against GBM cells. By offering an alternative route for antibody delivery through niosomal nanocarriers, these findings open new avenues for the development of more effective GBM therapeutics, warranting further non-clinical and clinical investigations.